2021
DOI: 10.3390/vaccines9101092
|View full text |Cite
|
Sign up to set email alerts
|

Waning of IgG, Total and Neutralizing Antibodies 6 Months Post-Vaccination with BNT162b2 in Healthcare Workers

Abstract: Data about the long-term duration of antibodies after SARS-CoV-2 vaccination are still scarce and are important to design vaccination strategies. In this study, 231 healthcare professionals received the two-dose regimen of BNT162b2. Of these, 158 were seronegative and 73 were seropositive at baseline. Samples were collected at several time points. The neutralizing antibodies (NAbs) and antibodies against the nucleocapsid and the spike protein of SARS-CoV-2 were measured. At day 180, a significant antibody decl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
106
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 49 publications
16
106
2
1
Order By: Relevance
“…Having these data in mind, it is difficult to definitely conclude that these tests showed a better ability to detect NAbs than the other tests evaluated in this study [5]. In addition, our group and others previously showed that the positivity threshold reported in the instructions for using the Roche Elecsys ® anti-SARS-CoV-2 spike is not a threshold for correlating with neutralization [6][7][8][9][10][11]. It was demonstrated that higher antibody titers are needed to correlate with seroneutralization although this is subject to the diversity of antibody response among individuals [7,11].…”
Section: Introductionmentioning
confidence: 63%
“…Having these data in mind, it is difficult to definitely conclude that these tests showed a better ability to detect NAbs than the other tests evaluated in this study [5]. In addition, our group and others previously showed that the positivity threshold reported in the instructions for using the Roche Elecsys ® anti-SARS-CoV-2 spike is not a threshold for correlating with neutralization [6][7][8][9][10][11]. It was demonstrated that higher antibody titers are needed to correlate with seroneutralization although this is subject to the diversity of antibody response among individuals [7,11].…”
Section: Introductionmentioning
confidence: 63%
“…Further on, all cited studies did not assess whether patients were infected by the Wuhan original strain or a variant strain, which, for the above reasons, could affect inter-assays harmonization. As to the study by Bayart et al [10] , which showed a much faster decline in neutralizing antibody titers using a live VNT than we assessed with our sVNT, available literature has so far provided contrasting results about long-term decay of circulating antibodies after mRNA vaccination, with some studies providing evidence for persistent and sustained neutralizing bioactivity of serum up to 6 months from vaccination [11] , [12] . It’s our opinion that such discrepancies are resulting from multiple factors, including but not limited to inter-assays inconsistencies, such as previous exposure to cross-reacting common cold coronaviruses, age, history of previous COVID-19, sex, and other comorbidities in vaccinated cohorts.…”
mentioning
confidence: 61%
“…On the other hand, as repeatedly shown by comparative analyses in vaccinated cohorts [7] , [8] , [9] , the diagnostic reliability of sVNT seems to be retained when assessing vaccine-induced immune-responses, provided that the mRNA sequence of the vaccine RBD matches that of the recombinant RBD in the binding and competition assays. The cross-sectional studies cited by Lippi and Plebani [5] , [6] quantified humoral immunogenicity markers in two cohorts of convalescent COVID-19 patients while the cohort studied by Bayart et al [10] is as well affected by a large number (31%) of individuals with a positive serological scrutiny for SARS-CoV-2 infection before vaccination. In fact, the primary aim of the study by Meyer et al [5] was the diagnostic value and comparability of different immune assay platforms for a diagnosis of SARS-CoV-2 infection rather than the long-term monitoring of the immune response to a spike-based vaccine.…”
mentioning
confidence: 99%
“…The most important information to integrate into the next phase of attack-rate estimation and population-immunity estimation in the US is the rate of antibody waning following SARS-CoV-2 infection and SARS-CoV-2 vaccination. Average waning rates are now known for the short-term post-infection [ 39 42 ] and post-vaccination [ 43 46 ][ 47 ], and this may be enough to estimate a recent attack rate [ 48 ] which can either be reported as such or chained together with other recent attack-rate estimates to provide an annual attack-rate estimate. Although the initial live integration of these data streams will no doubt be challenging, the benefit will be a situationally-aware susceptibility estimate that will allow us to evaluate the invasion ability of a new high-transmissibility variants (such as Alpha or Delta) or the inevitable immune-escape variants – like the Omicron lineage [ 49 , 50 ] – that will likely continue appearing in 2022 and 2023.…”
Section: Discussionmentioning
confidence: 99%